Logistics and Supply Chain Management on Industry Perspective: The Needs for Vocational High School Curriculum - Ahmad Ade Miftachudin (Universitas Negeri Surabaya, 2023)
The purpose of this study is to examine the logistics and supply chain management included in the independent curriculum in phase F for the Office Automation and Management Expertise Program for Vocational High School students with job needs in the industry. This is important because the main goal of the Vocational High School is to create graduates who are ready to work according to industry needs. This research was conducted using the Miles and Hubberman Model qualitative research, where this research was conducted at one of the well-known logistics and supply chain companies in Indonesia, namely J&T. Data collection in this study used observation, documentation, and interview techniques conducted by researchers directly to the objects studied at the J&T company. The results of this study indicate that in general the independent curriculum in phase F for the Office and Business Service Management Expertise Program on logistics and supply chain management is not fully following industry needs, a study on J&T companies. However, there are several job specifications and organizational structures that need to be understood by prospective graduates so that the skills learned at school can fully match the needs of the industry. In addition, teachers and students must learn the special characteristics possessed by logistics and supply chain companies in Indonesia so that specializing in concentration can help students prepare their skills to be fully absorbed by the workforce.